A prospective evaluation of real-time PCR assays for the detection of Orientia tsutsugamushi and Rickettsia spp. for early diagnosis of rickettsial infections during the acute phase of undifferentiated febrile illness. - Watthanaworawit, W; Turner, P; Turner, C; Tanganuchitcharnchai, A; Richards, A; Bourzac, K; Blacksell, S; Nosten, F (2013)
One hundred and eighty febrile patients were analyzed in a prospective evaluation of Orientia tsutsugamushi and Rickettsia spp. real-time polymerase chain reaction (PCR) assays for early diagnosis of rickettsial infections. By paired serology, 3.9% (7 of 180) and 6.1% (11 of 180) of patients were confirmed to have acute scrub or murine typhus, respectively. The PCR assays for the detection of O. tsutsugamushi and Rickettsia spp. had high specificity (99.4% [95% confidence interval (CI): 96.8-100] and 100% [95% CI: 97.8-100], respectively). The PCR results were also compared with immunoglobulin M (IgM) immunofluorescence assay (IFA) on acute sera. For O. tsutsugamushi, PCR sensitivity was twice that of acute specimen IgM IFA (28.6% versus 14.3%; McNemar's P = 0.3). For Rickettsia spp., PCR was four times as sensitive as acute specimen IgM IFA (36.4% versus 9.1%; P = 0.08), although this was not statistically significant. Whole blood and buffy coat, but not serum, were acceptable specimens for these PCRs. Further evaluation of these assays in a larger prospective study is warranted.